The relationship between intellectual capital components and business performance of textile sector in Pakistan. - Ahmad, Riaz (2020)
Intellectual capital (IC) is among the organizational unique resources that could leverage business performance. However, ineffective development of IC by companies could negatively affect business performance. The main concern of this study is how different types of IC components are managed by companies to optimize their business performance. Considering the ongoing issues related to IC and its impact on business performance, the aim of this research is to investigate the impact of IC components on business performance of the textile companies listed on the Pakistan Stock Exchange (PSX). This study also examines the moderating effect of board characteristics on the relationship between the IC components and business performance. Using cross sectional research design, 422 sets of questionnaire were distributed among the senior managers of the textile companies by using stratified sampling technique which yielded a 69% response rate. Partial Least Square (PLS)-Structural Equation Modelling (SEM) approach was employed to analyze the data. The findings show that IC components like human capital, information capital and spiritual capital have positive significant influence on business performance. In contrast, social capital has negative significant influence on business performance. On the other hand, structural capital and relational capital have negative insignificant impact on business performance. Moreover, the findings inferred a significant moderating effect of board characteristics on the relationship between human capital, structural capital, social capital, spiritual capital and business performance. However, no moderating effect of board characteristics was found on the relationship between relational capital, information capital and business performance. This study contributes to the body of literature by suggesting role of board characteristics in strengthening the relationship between the IC components and business performance under the theoretical shadow of resource-based view as well as resource dependency. The study also provides valuable insights for corporations to capitalize their IC resources to sustain business performance.